Dundonald Hill Estate in urban Port of Spain Trinidad and Tobago : a case study in sustainable development - Pantin, Dennis (Caribbean Conservation Association St. MichaelBB, 1994)
Reviews the literature on sustainable development and its applicability to the Caribbean. Presents the case study and looks at macro-economic implications of achieving sustainable development in spontaneous settlements in Trinidad and Tobago. Examines the feasibility of realizing a sustainable national policy on spontaneous settlements in Trinidad and Tobago.